Randomized within‐subject trial to evaluate smokers’ initial perceptions, subjective effects and nicotine delivery across six vaporized nicotine products - Voos, Natalie; Kaiser, Lisa; Mahoney, Martin C.; Bradizza, Clara M.; Kozlowski, Lynn T.; Benowitz, Neal L.; O'Connor, Richard J.; Goniewicz, Maciej L. (Addiction (Abingdon, England), 2019)
Background and Aims Vaporized nicotine products (VNPs) can vary in important characteristics including size, shape, flavor and nicotine yield. We examined whether complex interactions among these characteristics could affect smokers’ VNP perceptions and usage patterns. Design A within‐subject randomized cross‐over trial. Setting Roswell Park Comprehensive Cancer Center, Buffalo, NY, USA. Participants Eighteen daily cigarette smokers. Measurements Participants attended eight weekly visits during which they sampled six different VNPs (disposable, rechargeable, eGO, mod, e‐Cigar and e‐Pipe) with tobacco‐flavored e‐liquid. Prior to device use, participants completed product‐ranking questionnaires. Participants completed controlled puffing sessions during each of the six trials, after which satisfaction questionnaires were completed and blood samples were taken. Findings Initial perceptions showed that the smallest device (disposable) was ranked as safer compared with a larger device (e‐Pipe) (P < 0.05). Participants rated the eGO and mod devices higher on satisfaction and enjoyment from use, taste, pleasantness, harshness (‘throat hit’) and speed of effect, but lower on perceived health risk and embarrassment from use (P < 0.05). All devices had a lower Cmax than the combustible cigarette (P < 0.05), but there were differences among devices (P < 0.05). The mod, e‐Pipe and eGO provided the highest amount of perceived smoking urge relief, and this correlated strongly with Cmax across all devices (R2 = 0.8614, P = 0.007). The perceived speed of urge relief was not correlated with Tmax (R2 = 0.0035, P = 0.911) Conclusions Daily cigarette smokers testing six types of vaporized nicotine products (VNPs) reported that they varied in taste, amount of withdrawal relief, harshness, embarrassment from use, perceived health risk and subjective and objective nicotine delivery. The eGO and mod models have properties that may make them most effective for cigarette substitution among smokers who intend to switch to a VNP.